Streptococcus mutans and Streptococcus sobrinus colonization and caries experience in 3- and 5-year-old Thai children - P. Saraithong (2018)
© 2015, Springer-Verlag Berlin Heidelberg. Objectives: The aim of this study was to examine the colonization of Streptococcus mutans and Streptococcus sobrinus in supra-gingival plaque samples and to determine their correlation with the prevalence of early childhood caries (ECC) in Thai children. Materials and methods: A total of 344 Thai children, ages 3 and 5 years, were invited to participate in this study. Caries status of the children was examined. Supra-gingival plaque samples were collected. Quantitative real-time PCR was performed to evaluate DNA levels of S. mutans and S. sobrinus. Results: Eighty-five percent of the children were colonized by S. mutans and 50.9 % of them were colonized by S. sobrinus. The prevalence of ECC was 43.8 % and 56.2 % among 3- and 5-year-old children, respectively, and was significantly associated with the presence of S. mutans and S. sobrinus. The severity of ECC was significantly correlated with increased DNA levels of the two bacteria. Children who were positive for S. mutans and S. sobrinus (Sm+/Sb+) were 8 times or 44 times more likely to experience ECC than children who were Sm−/Sb + or were Sm−/Sb−. Conclusions: The study evidence further suggest that children colonized by both S. mutans and S. sobrinus are at the higher risk for ECC. Clinical relevance: Molecular-based qPCR can be used to detect and quantify S. mutans and S. sobrinus colonization for epidemiological and clinical studies for ECC risk assessment.